The role of probiotics and prebiotics in modulating of the gut-brain axis - Ansari, Fereshteh; Neshat, Mehrdad; Pourjafar, Hadi; Jafari, Seid Mahdi; Samakkhah, Shohreh Alian; Mirzakhani, Esmaeel (Frontiers in Nutrition, 2023)
Pro-and prebiotics have been indicated to modulate the gut-brain axis, which have supportive impacts on central nervous systems, and decrease or control the incidence of some mental disorders such as depression, anxiety, autism, Schizophrenia, and Alzheimer. In this review, complex communications among microbiota, gut, and the brain, and also recent scientific findings of the impacts and possible action mechanisms of pro-and prebiotics on mental disorders have been discussed. The results have shown that pro-and prebiotics can improve the function of central nervous system and play an important role in the prevention and treatment of some brain disorders; however, in order to prove these effects conclusively and firmly and to use these compounds in a therapeutic and supportive way, more studies are needed, especially human studies/clinical trials.